Research of the life cycle for two most common routes of steel production with a focus on the impact to the human body - Ivanna Harasymchuk; Vladimír Kočí; Tatiana Trecáková (International Journal of Sustainable Engineering)
The metallurgical industry simultaneously represents both one of the most crucial sectors of the industry and a sector with significant emissions. Alongside methods to mitigate the harmful impact on the environment, we need to consider reducing the hazardous, toxicological impact on the human organism. In this article, we explore the life cycle of two steel production methods: BF-BOF and EAF. The results of our research indicate that the EAF method has a lesser impact on the human organism. Our goal is to identify the key processes that constitute the primary source of emissions of hazardous substances in each of these two pathways. We investigated the distribution of the impact of production processes in each of the two aforementioned methods. In traditional steel production using oxygen converters, the primary source of emissions is the production of pig iron in blast furnaces. In the second case, it was the used electricity. For this study, we applied the LCA methodology, which enables determining the impact of the investigated process throughout its entire life cycle. In the conclusion, possible options for mitigating the harmful impact of each case are discussed.